Mathematics higher level topic 8 - option : sets, relations and groups for the IB diploma - Fannon, Paul, ....-; Kadelburg, Vesna, ....-; Woolley, Ben, ....- (Cambridge : Cambridge University Press, 2013)
For students studying either the mathematics higher level course or further mathematics, this book covers all the material in the Sets, Relations and Groups option (option number 8) in print. This highly illustrated book is based on the new group 5 aims forms part of the completely new Mathematics for the IB Diploma series, Cambridge's comprehensive coverage of IB diploma mathematics for then 2012 SL and HL courses. Features include: a sections of mixed examination questions; plenty of worked examples; questions colour-coded according to grade; exam-style questions; feature boxes of hints and tips. Written to specifically cover the new IB Higher Level option in Sets, Relations and Groups, it is a fantastic guide to the material in this option, no matter which book is being used to cover the core material.
Includes index.
Keywords: Relaties (wiskunde).; Groepen (wiskunde).